2014
DOI: 10.1111/vec.12154
|View full text |Cite
|
Sign up to set email alerts
|

Decreased central venous oxygen saturation despite normalization of heart rate and blood pressure post shock resuscitation in sick dogs

Abstract: Decreased ScvO2 exists in a significant proportion of critically ill dogs following standard fluid resuscitation for shock, providing a relevant target population for implementation of a more standardized early goal-directed therapy bundle in veterinary patients. Normalization of heart rate, blood pressure, mentation, and perfusion parameters directed by physical examination may be attained despite the persistence of significant tissue hypoperfusion and oxygen debt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
0
15
0
1
Order By: Relevance
“…[84][85][86] In a recent prospective, observational trial including 30 dogs in hypovolemic or septic shock, central venous [LAC] remained ࣙ2 mmol/L in 7/30 (23%) of patients and ScvO 2 remained < 70% in 11/30 (38%) of patients despite normalization of traditional hemodynamic parameters including heart rate and blood pressure. 87 These results highlight the importance of using multiple clinical end points to assess the efficacy of shock resuscitation.…”
Section: Veterinary Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…[84][85][86] In a recent prospective, observational trial including 30 dogs in hypovolemic or septic shock, central venous [LAC] remained ࣙ2 mmol/L in 7/30 (23%) of patients and ScvO 2 remained < 70% in 11/30 (38%) of patients despite normalization of traditional hemodynamic parameters including heart rate and blood pressure. 87 These results highlight the importance of using multiple clinical end points to assess the efficacy of shock resuscitation.…”
Section: Veterinary Literaturementioning
confidence: 96%
“…Experimental trials in animals have also demonstrated that normalization of traditional hemodynamic parameters including heart rate and blood pressure do not necessarily guarantee adequate oxygen delivery at the capillary level . In a recent prospective, observational trial including 30 dogs in hypovolemic or septic shock, central venous [LAC] remained ≥2 mmol/L in 7/30 (23%) of patients and ScvO 2 remained < 70% in 11/30 (38%) of patients despite normalization of traditional hemodynamic parameters including heart rate and blood pressure . These results highlight the importance of using multiple clinical end points to assess the efficacy of shock resuscitation.…”
Section: Lactate As a Therapeutic Guidementioning
confidence: 99%
“…Tissue hypoperfusion can, however, be present despite normal standard hemodynamic variables, a phenomenon termed “occult shock.” In a recent clinical trial, dogs presenting in hypovolemic or septic shock were resuscitated to satisfy traditional hemodynamic targets. In this study, 6/30 dogs had persistently increased plama lactate concentrations and 11/30 dogs had persistently low ScvO 2 (<70%), suggesting ongoing tissue hypoperfusion despite normalization of routine hemodynamic parameters . The hyperlactatemia of shock is unlikely to be solely due to impaired oxygen delivery leading to increased anaerobic metabolism.…”
Section: Pathophysiology–dyshomeostasis In Diseasementioning
confidence: 59%
“…A normal ScvO 2 range has never been established in veterinary patients; however, the cutoff of 70% has been suggested based on the experimental work and experience in human medicine. Using that cutoff in one study, 11/30 critically ill dogs were suspected to have occult shock despite normalization of heart rate, blood pressure, mentation, and perfusion parameters, suggesting persistent severe illness despite clinical findings suggesting otherwise . Dogs that had a ScvO 2 >70% were also noted to have improved normalization of lactate, suggesting better reversal of shock in those patients.…”
Section: Scvo2 In Veterinary Medicinementioning
confidence: 99%